Penyuluhan Ekonomi Kreatif pada Nilai Guna Media Tanam Organik Melalui Sekam Bakar Ibu – Ibu Rumah Tangga Desa Manarap Baru Kalimantan Selatan (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This community service program was conducted in Manarap Baru Village, Banjar Regency, South Kalimantan, focusing on the utilization of rice husks as a planting medium to promote creative economic development. The background of this initiative stems from the local soil conditions, which are predominantly fill soil and swamp, making it less suitable for plant cultivation. Additionally, the community—especially housewives—faces limited knowledge and resources in processing agricultural waste into economically valuable products. The implementation methods included preliminary surveys, socialization, educational outreach, hands-on practice, and evaluation. The materials delivered covered the benefits of rice husks as planting media and compost, techniques for converting husks into charcoal, and business opportunities derived from processed husk products.The results of the program showed a significant improvement in participants' understanding of independent planting media and compost production, reduced reliance on commercial products, and the emergence of new business opportunities that support sustainable agriculture.